Sustainable cassava: Strategies from production through waste management - Ogwu, Matthew Chidozie; Izah, Sylvester Chibueze; Alves, Alfredo Augusto Cunha; Babu, Suresh Chandra (Academic Press, 2024)
Sustainable Cassava: Strategies from Production through Waste Management presents viable approaches to promote sustainability in this globally important crop, enabling future generations to benefit. Presented in three parts, the first addresses cassava diversity and distribution, sustainable production and cultivation practices, and root processing innovations of the crop. Cassava trade policies and economic value chains, food safety and use of cassava, and agro-industrial cassava products are addressed in the second part. The third part focuses on bioeconomy aspects, cassava waste quality assessment, toxicology, sanitary practices, environmental risk assessment as well as sustainable management strategies for cassava waste using biotechnological and industrial advances.